The Influence of Workload and Compensation on Employee Job Satisfaction at Aisyiyah Hospital Purworejo - Astuti, Retno; Samsudin, Mohammad Agus (Dinasti International Journal of Management Science, 2025)
Employee job satisfaction is an essential factor in achieving organizational goals, particularly in the health care sector. In hospitals, high job satisfaction supports the quality of patient services. Workload and compensation are among the factors believed to influence job satisfaction. A workload that matches employees’ abilities and fair compensation can increase motivation and satisfaction. This study aims to analyze the effect of workload and compensation on employee job satisfaction at Aisyiyah General Hospital Purworejo. The research employed a quantitative approach with purposive sampling involving 86 respondents. Data were collected using a questionnaire and analyzed through multiple linear regression with IBM SPSS 25. The results revealed that (1) workload has a positive and significant effect on employee job satisfaction, (2) compensation has a positive and significant effect on employee job satisfaction, and (3) workload and compensation simultaneously have a significant effect on employee job satisfaction. Appropriate workload and fair compensation are key factors in enhancing employee job satisfaction, motivation, and loyalty at Aisyiyah General Hospital Purworejo.